2021
DOI: 10.1186/s13006-021-00407-y
|View full text |Cite
|
Sign up to set email alerts
|

Good practices in perinatal care and breastfeeding protection during the first wave of the COVID-19 pandemic: a national situation analysis among BFHI maternity hospitals in Spain

Abstract: Background Although the positive effects of good clinical quality standards in perinatal care and breastfeeding support for women, newborns and families have been already demonstrated, many of these practices were disrupted during the COVID-19 pandemic. The objective of this study was to analyse the impact of the COVID-19 pandemic on perinatal care and breastfeeding support practices offered by the Spanish maternity hospitals committed to the UNICEF Baby-friendly Hospital Initiative (BFHI), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
3
12
0
3
Order By: Relevance
“…A large multicenter study has also confirmed that rooming-in is feasible and recommended even for mothers hospitalized with a nonsevere form of COVID-19, with evident benefits on the initiation and maintenance of breastfeeding [25]. A survey conducted in Spain by Muñoz-Amat et al [26] described well which standards of care relating to childbirth and the postpartum period have been changed due to the pandemic. However, the same authors have shown how the structures committed to the UNICEF Baby-Friendly Hospital Initiative (BFHI) managed to guarantee standards of care and procedures similar to those before the pandemic and provided better support for mothers with and without COVID-19.…”
Section: Possible Strategies For Breastfeeding Protection and Promotionmentioning
confidence: 99%
“…A large multicenter study has also confirmed that rooming-in is feasible and recommended even for mothers hospitalized with a nonsevere form of COVID-19, with evident benefits on the initiation and maintenance of breastfeeding [25]. A survey conducted in Spain by Muñoz-Amat et al [26] described well which standards of care relating to childbirth and the postpartum period have been changed due to the pandemic. However, the same authors have shown how the structures committed to the UNICEF Baby-Friendly Hospital Initiative (BFHI) managed to guarantee standards of care and procedures similar to those before the pandemic and provided better support for mothers with and without COVID-19.…”
Section: Possible Strategies For Breastfeeding Protection and Promotionmentioning
confidence: 99%
“…Um número significativo de maternidades espanholas restringiu a presença do acompanhante, durante todo o processo de parto, nascimento e alojamento conjunto, bem como muitas das maternidades proibiram o contato pele a pele. Observou também que as nas regiões onde a pandemia foi mais severa ocorreu o contrário, ou seja, foram feitas menos restrições e permitido o acompanhante durante todo o tempo de hospitalização (Muñoz, Pallás & Hernández, 2021).…”
Section: Discussionunclassified
“…Step seen to have increased in hospitals in Italy and most of the newborn care took place in the mother's room [91]. This was also found in Spain [92]. However, it was reported in the Italian study that earlier discharge due to COVID-19 took away some professional support.…”
Section: Pattern 3: Implementation Of Speci C Stepsmentioning
confidence: 97%